THE EFFECT OF THE BOARD OF DIRECTORS ON FIRM PERFORMANCE: THE MODERATING ROLE OF FAMILY OWNERSHIP - Virdausy Salhami, Mas Tifanny; Armadani, Armadani (Faculty of Economics and Business University of Mataram, 2024)
This study aims to empirically test the influence of the board of directors on company performance with family ownership as a moderating variable. The sampling method used in this research was purposive sampling of manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period, resulting in 721 observations as a sample. The analysis technique applied to test the hypothesis is moderated regression analysis (MRA). This study empirically shows that female directors and larger boards will improve firm performance. However, family ownership reduces the positive impact of female directors on firm performance. Finally, family ownership does not strengthen the influence of board size on firm performance. This research provides an interesting view regarding the moderating role of family ownership on the effect of the board of directors on firm performance, which is analyzed comprehensively using two measurement proxies.